C‐X3‐C motif chemokine ligand 1/receptor 1 regulates the M1 polarization and chemotaxis of macrophages after hypoxia/reoxygenation injury. Issue 4 (1st December 2021) - Guo, Shuiming; Dong, Lei; Li, Junhua; Chen, Yuetao; Yao, Ying; Zeng, Rui; Shushakova, Nelli; Haller, Hermann; Xu, Gang; Rong, Song
Abstract: Background: Macrophages play an important role in renal ischemia reperfusion injury, but the functional changes of macrophages under hypoxia/reoxygenation and the related mechanism are unclear and need to be further clarified. Methods: The effects of hypoxia/reoxygenation on functional characteristics of RAW264.7 macrophages were analyzed through the protein expression detection of pro‐inflammatory factors TNF‐α and CD80, anti‐inflammatory factors ARG‐1 and CD206. The functional implications of C‐X3‐C motif chemokine receptor 1(CX3CR1) down‐regulation in hypoxic macrophages were explored using small interfering RNA technology. Significance was assessed by the parametric t ‐test or nonparametric Mann–Whitney test for two group comparisons, and a one‐way ANOVA or the Kruskal–Wallis test for multiple group comparisons. Results: Hypoxia/reoxygenation significantly increased the protein expression of M1‐related pro‐inflammatory factors TNF‐α, CD80 and chemokine C‐X3‐C motif chemokine ligand 1 (CX3CL1)/CX3CR1 and inhibited the protein expression of M2‐related anti‐inflammatory factors ARG‐1 and CD206 in a time‐dependent manner in RAW264.7 cells. However, the silencing of CX3CR1 in RAW264.7 cells using specific CX3CR1‐siRNA, significantly attenuated the increase in protein expression of TNF‐α ( P <  0.05) and CD80 ( P <  0.01) and the inhibition of ARG‐1 ( P <  0.01) and CD206 ( P <  0.01) induced by hypoxia/reoxygenation. In addition, we also found that hypoxia/reoxygenation could significantly enhance the migration (2.2‐fold, P <  0.01) and adhesion capacity (1.5‐fold, P <  0.01) of RAW264.7 macrophages compared with the control group, and CX3CR1‐siRNA had an inhibitory role (40% and 20% reduction, respectively). For elucidating the mechanism, we showed that the phosphorylation levels of ERK ( P <  0.01) and the p65 subunit of NF‐κB ( P <  0.01) of the RAW264.7 cells in the hypoxic/reoxygenation group were significantly increased, which could be attenuated by down‐regulation of CX3CR1 expression ( P <  0.01, both). ERK inhibitors also significantly blocked the effects of hypoxic/reoxygenation on the protein expression of M1‐related pro‐inflammatory factors TNF‐α, CD80 and M2‐related anti‐inflammatory factors ARG‐1 and CD206. Moreover, we found that conditioned medium from polarized M1 macrophages induced by hypoxia/reoxygenation, notably increased the degree of apoptosis of hypoxia/reoxygenation‐induced TCMK‐1 cells, and promoted the protein expression of pro‐apoptotic proteins bax ( P <  0.01) and cleaved‐caspase 3 ( P <  0.01) and inhibited the expression of anti‐apoptotic protein bcl‐2 ( P <  0.01), but silencing CX3CR1 in macrophages had a protective role. Finally, we also found that the secretion of soluble CX3CL1 in RAW264.7 macrophages under hypoxia/reoxygenation was significantly increased. Conclusions: The findings suggest that hypoxia/reoxygenation could promote M1 polarization, cell migration, and adhesion of macrophages, and that polarized macrophages induce further apoptosis of hypoxic renal tubular epithelial cells by regulating of CX3CL1/CX3CR1 signaling pathway.